Growth and Carrageenan Yield of Cultivated Kappaphycus alvarezii (Doty) in Deep Seawater Area of Saparua Bay, Central Maluku - Wenno, Petrus A; Latumahina, Matheus Ch.A; Loupatty, Sven R.; Soumokil, Agustina W.; Jamal, Endang (Aquacultura Indonesiana, 2018)
Cultivation of Kappaphycus alvarezii has been carried out by inverted pyramid method in the deep water of  Saparua Bay. This study aims to analyze the daily growth rates, biomass productions and carrageenan yields of the green and brown strain of K. alvarezii with different depth of water by inverted pyramid method in deep seawaters. K. alvarezii with an initial weight of 100 g were planted successively at the depths of 1, 3, 5, 7 and 9 m during four growing seasons that last for 49 days in every season. The results showed that the highest growth rate and biomass production were on green strain at 1 m depth and brown strain at 3 m depth which were 4.18% and 749.29 g/m2 then 4.19% and 754.51 g/m2, respectively. While the highest carrageenan yield was on the green and brown strain at 9 m depth which were 16.53% and 14.85%, respectively. The carrageenan yields gradually increase with the increasing of water depths which contradict to growth rate and biomass production that showed the better results at lower depths (1 and 3 m). In conclusion, seaweed cultivation in deep waters has a positive impact on carrageenan yields in line with the increasing depths while the growth rate and the biomass production can be achieved higher at the lower depth.